Exploring undergraduate student perception of international student mobility program - Susanti, Ani; Pratolo, Bambang Widi; Khusnawati, Khusnawati (English Language Teaching Educational Journal, 2024)
In recent years, the international student mobility program has been popular among university students. In 2017, there were over 5.3 million international students spread globally. The aim of this study is to determine the perception of undergraduate students about the advantages and challenges of International Student Mobility Programs that they have participated in. The subject of this research is students of the English Education Study Program at Universitas Ahmad Dahlan who have joined International Student Mobility Programs. This study used a qualitative research method and the data will be obtained from interviews with the research subjects. The findings in this research are divided into the advantages and the challenges of international student mobility. The advantages of participating in the international student mobility program are language learning, expand the networks, learn new culture, and self-development. There are several challenges that students feel while participating in the international student mobility program, namely language difference, difference habit, study materials and heavier assignments, and time difference. The results of this research will be useful for students who will take part in the international student mobility program in order to better understand the benefits and challenges that are usually experienced by international student mobility participants.